PROPERTIES OF FORESHOCKS AND AFTERSHOCKS IN THE AREA OF GREECE - Kourouzidis, M. C.; Karakaisis, G. F.; Papazachos, B. C.; Makropoulos, C. (Bulletin of the Geological Society of Greece, 2004)
The results of the study of seismic sequences of all the mainshocks with M>5.6 during 1911-1965 and M>5.0 during 1966-1985 which occurred in the Aegean and surrounding area are presented. As regards the foreshocks, two relations have been proposed that can be used to determine (1) the probability that at least one foreshock, with magnitude Mf or larger, will precede a strong (M>6.0) earthquake, and (2) the probability for the largest foreshock to occur during t days before the mainshock. It was also found that the rate of foreshock occurrence, N(TS), increases as the time of the mainshock approaches and is described by a power-law function. The time and magnitude distribution of several foreshock sequences were also studied. The study of aftershock sequences concerned properties of their largest aftershock, the dependence of the duration and number of the aftershocks on the magnitude of the mainshock and the time and magnitude distribution of several aftershock sequences. The conclusion is that the study of a seismic excitation which is based on continuous monitoring and fast determination of the basic focal parameters of the earthquakes can contribute to clarify whether this activity evolves normally or not.